Case report: Unilateral transnasal endoscopic marsupialization of nasopalatine duct cyst - Kagoya, Ryoji; Iwanami, Tomoko; Mochizuki, Makoto; Kondo, Kenji; Ito, Ken (Frontiers in Surgery, 2022)
Nasopalatine duct cyst (NPDC) is the most common type of non-odontogenic cysts of the jaw. It has been treated with complete surgical resection using a sublabial or palatine approach. However, complete removal of the cyst can be accompanied by postoperative complications including oronasal fistula. Recently, endoscopic marsupialization for the disease has been advocated, but there are still few reports regarding the surgery. Herein, we report a case of NPDC that was treated with unilateral transnasal endoscopic marsupialization. A 43-year-old man with no relevant previous medical history was referred to our hospital for the treatment of lesion occupying the right nasal cavity. A computerized tomography scan of the sinus revealed an egg-shaped lesion with a well-defined border centered on the lower half of the nasal cavity and hard palate. Based on the site of the lesion, it was considered to be NPDC. Transnasal endoscopic marsupialization was performed to diagnose and improve nasal obstruction. Histopathological examination revealed stratified squamous epithelium without atypia, which was consistent with NPDC. Although the patient noticed paresthesia of the right upper incisor area, symptoms improved 3 months after surgery. Written informed consent was obtained from the patient for the publication of any potentially identifiable images or data included in this article. Transnasal endoscopic marsupialization for NPDC is minimally invasive and useful; however, it is necessary to build evidence for an appropriate excision range based on the position and size of the lesion.